Can Pediatricians Assess Exercise-Induced Bronchoconstriction From Post-exercise Videos? - Lammers, N.; van Hoesel, M. H. T.; Brusse-Keizer, M. G. J.; van der Palen, J.; Spenkelink-Visser, R.; Driessen, J. M. M.; Thio, B. J. (Frontiers in Pediatrics, 2020)
Exercise-induced bronchoconstriction (EIB) is a highly prevalent morbidity of childhood asthma and defined by a transient narrowing of the airways during or after physical exercise. An exercise challenge test (ECT) is the reference standard for the diagnosis of EIB. Video evaluation of EIB symptoms could be a practical alternative for the assessment of EIB. We studied the ability of pediatricians to assess EIB from post-exercise videos. A clinical assessment was performed in 20 asthmatic children (mean age 11.6 years) and EIB was measured with a standardized ECT performed in cold, dry air. EIB was defined as a fall in forced expiratory volume in 1 second (FEV1) of ≥10% post-exercise. Children were filmed before and after exercise in frontal position and bare chested. The clinical assessment results and videos were shown to 20 pediatricians (mean experience 14.4 years). Each assessed EIB severity in 5 random children providing 100 assessments, scored on a continuous rating scale (0-10) and in severity classifications (no, mild, moderate, severe) using a scoring list including physical asthma symptoms. Correlations between predicted scores and objective scores were calculated with Spearman’s rho and Cohen’s Kappa. A generalized linear model was used to assess the relationship between physical symptoms and fall in FEV1. Median fall in FEV1 after exercise was 15.1% (IQR 1.2-65.1). Pediatricians detected EIB with a sensitivity of 78% (95% CI 66%-87%) and a specificity of 40% (95% CI 27%-55%). The positive predictive value for a pediatricians’ diagnosis of EIB was 61% (95% CI 50%-72%). The negative predictive value was 60% (95% CI 42%-76%). The agreement between predicted EIB severity classifications and the validated classifications based on the ECT’s, was fair (Kappa = 0.36 (95% CI 0.23-0.48)). The correlation between predicted EIB severity scored on a continuous rating scale and fall in FEV1 after exercise was weak (rs = 0.39, p <0.001). Independent predictive variables for fall in FEV1 were wheezing (-11%), supraclavicular retractions (- 8.4%) and a prolonged expiratory phase (-8.8%). The ability of pediatricians to assess EIB from post-exercise videos is fair at best, implicating that standardized ECT’s are still vital in the assessment of EIB.